Development of a Reverse Genetic System to Generate Recombinant Chimeric Tacaribe Virus that Expresses Junín Virus Glycoproteins - Foscaldi, Sabrina Andrea (2020)
Mammarenaviruses are enveloped and segmented negative-stranded RNA viruses that comprise several pathogenic members associated with severe human hemorrhagic fevers. Tacaribe virus (TCRV) is the prototype for the New World group of mammarenaviruses and is not only naturally attenuated but also phylogenetically and antigenically related to all South American pathogenic mammarenaviruses, particularly the Junín virus (JUNV), which is the etiological agent of Argentinian hemorrhagic fever (AHF). Moreover, since TCRV protects guinea pigs and non-human primates from lethal challenges with pathogenic strains of JUNV, it has already been considered as a potential live-attenuated virus vaccine candidate against AHF. Here, we report the development of a reverse genetic system that relies on T7 polymerase-driven intracellular expression of the complementary copy (antigenome) of both viral S and L RNA segments. Using this approach, we successfully recovered recombinant TCRV (rTCRV) that displayed growth properties resembling those of authentic TCRV. We also generated a chimeric recombinant TCRV expressing the JUNV glycoproteins, which propagated similarly to wild-type rTCRV. Moreover, a controlled modification within the S RNA 5′ non-coding terminal sequence diminished rTCRV propagation in a cell-type dependent manner, giving rise to new perspectives where the incorporation of additional attenuation markers could contribute to develop safe rTCRV-based vaccines against pathogenic mammarenaviruses.